Analisis Pengaruh Wisata Halal terhadap Kepuasan Pengunjung dan Minat Berkunjung Kembali (Studi Kasus Wisata Halal di Kota Bandung) - Yapanto, Azriel Mohamad; Cupian, Cupian (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
This study aims to analyze the effect of halal tourism on visitor satisfaction and interest in visiting again, with a case study in Bandung City. Halal tourism is a tourism concept that meets halal requirements, not only on food, but also on all aspects of services and facilitiesThe method used in this study is quantitative, with primary data collection through questionnaires distributed to visitors at several halal tourist sites in Bandung. Respondents in this study were tourists who visited these locations. Data analysis is done using Structural Equation Modeling (SEM-PLS), which helps in testing and analyzing relationships between variables. The results of the study show that aspects of halal tourism in Bandung, such as the availability of halal food, worship facilities, and services that are in accordance with Islamic principles, have a significant influence on visitor satisfaction. This has a positive effect on the interest of visitors. to revisit the tourist site. This shows that a satisfactory halal tourism experience can encourage tourists to make repeat visits his has a positive effect on the interest of visitors to revisit the tourist site. This shows that a satisfactory halal tourism experience can encourage tourists to make repeat visits. These findings have important implications for tourism developers and city governments, particularly in terms of halal tourism development strategies. The study also provides insight into future research.